Translation of artistic means in the story of B. Sokpakbaev "My name is Kozha" into Russian and English (Eurasian Journal of Philology Science and Education, 2023)
Nowadays, many writers use artistic means in their works to impress the recipients of the work and demonstrate their skill. The instructive, aesthetic, cognitive nature of works for children will differ from other styles and literary genres.In the story of the writer B. Sokpakbaev "My name is Kozha" there are many metaphors, epithets, comparisons, metonyms.Issues such as the linguistic personality and cognitive aspect of the heroes of this story, the character and setting, conflict, were considered by Kazakh literary critics and linguists, but the features of the translated versions of the original literary means into Russian and English were not mentioned.The features of the translation of literary means into stories, which served as the basis for this article, are analyzed using a comparative method using the theory and concept of a qualified Russian scientist of the translation industry V.N. Komissarov, associated with 5 levels of equivalence.The story of the writer Berdibek Sokpakbaev “My name is Kozha” is considered one of the works that was admired not only by Kazakh readers, but also by Russian and English recipients, although the analysis of the translation of literary means in three languages requires special study and contributes to the development of Kazakh translation studies.                 Key words: B. Sokpakbaev, My name is Kozha, artistic means, translation, transformation, original, recipient.